Iron monitoring of male and female rugby sevens players over an international season - Clarke, A. C.; Anson, J. M.; Dziedzic, C. E.; Mcdonald, W. A.; Pyne, D. B. (The Journal of Sports Medicine and Physical Fitness, 2018)
BACKGROUND: Given the likely influence that high training loads, contact-induced hemolysis and female-specific requirements have on the incidence of iron deficiency, characterizing the direction and magnitude of fluctuations in iron status over an international season is important for managing player health and physical performance in rugby sevens. METHODS: Australian national male (N.=27) and female (N.=23) rugby sevens players undertook blood tests at pre-season, mid-season, and end-season. Hemoglobin (Hb), hematocrit (Hct), ferritin, transferrin and transferrin saturation were quantified. Female athletes also reported oral contraceptive use and a subset (N.=7) provided 7-day food diaries to quantify iron intake. RESULTS: Male players typically had a three-fold higher ferritin concentration than females. Pre-season ferritin concentrations in male (151±66 µg/L) and female (51±24 µg/L) players declined substantially (~20%) by mid-season but recovered by end-season. Over the season 23% of female players were classified as iron deficient (ferritin <30 µg/L) and prescribed supplementation. The greatest incidence of iron deficiency in female players occurred mid-season (30%). Oral contraception and dietary iron intake had an unclear influence on female players` ferritin concentration, while age was largely positively correlated (r=0.66±~0.33). CONCLUSIONS: Given the relatively low ferritin concentrations evident in female rugby sevens players, and the potential for a further decline midway through a season when physical load may be at its highest, 6-monthly hematological reviews are suggested in combination with dietary management. Annual screening may be beneficial for male players, with further monitoring only when clinically indicated.